فعالية استخدام طريقة الاستجابة الجسدية الكاملة في تعليم مهارة الاستماع بمدرسة المنورة المتوسطة الإسلامية تاجينان - Muzadi, Narul Hasyim (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
In the process of learning language, one of the four language skills, listening is a basic skill that must be mastered by students in learning language before speaking, reading and writing skills. Low interest in listening results in less effective Arabic language learning. The method of delivery using conventional and less varied methods can influence students' interest and motivation to learn listening skills. Thus, researchers decided to use the Total Physical Response (TPR) method. This method contains elements of body movement and visualization to help students understand and remember new vocabulary. This study aims to describe the determine the effectiveness of the Total Physical Response method in teaching listening skills at MTs Al-Munawwaroh Tajinan. This study used a quantitative approach with data collection techniques using Test (Pretest-posttest). The results of the N-Gain Score show that the use of the Total Physical Response (TPR) method in the experimental group is quite effective with an average N-gain score of 66.26%. And the control group is less effective at learning using conventional methods with an average N-Gain score of 44.60%. As for the output of the Independent samples Test, it is known that the value of Sig. (2-tailed) of 0.003 < 0.05, Therefore, as the basis for decision making in the independent sample t test, it can be concluded that learning listening skills using the Total Physical Response method in grade VIII MTs Al-Munawwaroh Tajinan students is more effective than learning using conventional methods.